2015
DOI: 10.1016/j.inat.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Isolated trochlear nerve schwannoma presenting with diplopia: A case report and literature review

Abstract: Background: Trochlear nerve schwannoma is a very rare tumor encountered especially in patients without type 2 neurofibromatosis (NF2). Most of the time, this tumor is diagnosed intraoperatively. We describe a rare case of trochlear nerve schwannoma. Clinical Presentation: A 63-year-old male presented with generalized headache from 8 months earlier, without nausea and vomiting. The headache had worsened during the last months. Clinically, he suffered from transient diplopia. Magnetic resonance imaging (MRI) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Our patient presented with a tumor larger than the reported by 2015 by Jia Li et al of 32 x 18 x 8 compared to our case of 60 x 24 x 10mm causing asymmetry and proptosis [7]. In the orbit, schwannomas are usually unilateral and can develop from the supraorbitary, infraorbitary, supratrochlear, ciliary, oculomotor, trochlear or abducens nerve [1,[3][4][5][6][7].…”
Section: Discussioncontrasting
confidence: 39%
See 4 more Smart Citations
“…Our patient presented with a tumor larger than the reported by 2015 by Jia Li et al of 32 x 18 x 8 compared to our case of 60 x 24 x 10mm causing asymmetry and proptosis [7]. In the orbit, schwannomas are usually unilateral and can develop from the supraorbitary, infraorbitary, supratrochlear, ciliary, oculomotor, trochlear or abducens nerve [1,[3][4][5][6][7].…”
Section: Discussioncontrasting
confidence: 39%
“…The nerve of origin is not identified in up to 50% of cases 2, in our patient's case the surgical removal was difficult because of the superior oblique tendon affection. Highly cellular tumors have a higher recurrence rate and malignant transformation, thus early removal is recommended [1,[2][3][4]7]. Follow up of our patient at 3 years showed that he is asymptomatic and does not have any recurrence.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations